2015
DOI: 10.1155/2015/693025
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of the Tibial Baseplate in Bicompartmental Knee Arthroplasty

Abstract: Introduction. Bicompartmental knee arthroplasty (BKA) addresses combined medial and patellofemoral compartment osteoarthritis, which is relatively common, and has been proposed as a bridge between unicompartmental and total knee arthroplasty (TKA). Case Presentation. We present the case report of a young active man treated with BKA after unsuccessful conservative therapy. Four years later, loosening with fracture of the tibial baseplate was identified and the patient was revised to TKA. Discussion. Although ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Palumbo et al reported 14% of knees required revision to TKA at a mean 21 months post-surgery for persistent pain at the anterior medial aspect of the proximal tibia, with the authors also reporting that all tibial baseplates were grossly loose and easily explanted at the time of revision surgery [24]. The tibial baseplate was fractured in one which is a rare cause of implant failure in the knee but has been noted with the Journey-Deuce in other studies [36]. This demonstrates an inherent design law in the tibial component likely to be a baseplate that is too thin.…”
Section: Discussionmentioning
confidence: 95%
“…Palumbo et al reported 14% of knees required revision to TKA at a mean 21 months post-surgery for persistent pain at the anterior medial aspect of the proximal tibia, with the authors also reporting that all tibial baseplates were grossly loose and easily explanted at the time of revision surgery [24]. The tibial baseplate was fractured in one which is a rare cause of implant failure in the knee but has been noted with the Journey-Deuce in other studies [36]. This demonstrates an inherent design law in the tibial component likely to be a baseplate that is too thin.…”
Section: Discussionmentioning
confidence: 95%